Hubungan Kepatuhan Diet Dm Dengan Sisa Makanan Dan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Di Ruang Rawat Inap RSUD Sanjiwani Gianyar - Pramitha Mas Agustina; Pande Putu Sri Sugiani; Lely Cintari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
The success of the organization of food can be assessed from the patient's food waste indicator. The waste of food is an indicator of the success of nutrition therapy provided by the hospital. The remaining food exceeding 20% indicates a failure in a hospital food operation. In this case, the remaining food that is seen is the remaining food for Diabetes Mellitus patients. The high prevalence of Diabetes Mellitus is necessary for prevention efforts such as give education, food regulation, physical activity, drug consumption behavior, and checking blood glucose levels regularly. In a patient's eating setting, the success of controlling the patient’s blood glucose levels depends on the patient's compliance with running the DM diet. The aim of the research is to determine the relationship of DM diet obedience with food waste and blood glucose levels in patients with diabetes mellitus at Hospital Sanjiwani Gianyar. This research uses the observation method, with a Cross-Sectional approach. Data collection using questionnaires and weigher. The sample of this study amounted to 36 people. The test used is Spearman Test. The result of DM diet obedience classified as non-adherent and adherent there are 88,89 % and 11,11%. The results of the spearman test analysis for DM dietary compliance with food residue and blood glucose levels obtained p = 0.000 (p 0.05) which means there is a significant relationship between DM diet obedience with food waste and blood glucose levels.Keywords: Diet Obedience; Food Waste; Blood Glucose Level; Diabetes Mellitus